Geodetic support of the territory of Chernivtsi oblast (history, current state) - Trevogo, Igor; Sukhiy, Petro; Bilokrynytskiy, Sergij; Darchuk, Kostiantyn (Національний університет «Львівська політехніка», 2020)
The purpose of the research is to substantiate the theoretical and scientific-methodical bases of the im-portance of geodetic support of the territories of the regions, to assess the possibility of creating topo-graphic maps and plans of one or another scale on the existing geodetic network. To achieve the purpose of the research, the following methods and techniques were used: historical analysis (to study the history of geodetic support), geodetic (to determine the required density of geodetic points when conducting topographic surveys without violating regulations), mathematical (to determine the completion of the geodetic network, assessments of the possibility of creating topographic maps and plans for a particular area), methods of cartography (to display the points of geodetic support) and oth-ers. The history of research of geodetic support of the regions of the territory of Ukraine is hundreds of years old, but only, in our opinion, in recent years (the years of independence of Ukraine) they have acquired a scientific character. The analysis of geodetic support of the territory of Chernivtsi oblast is carried out. The possibility of creating topographic maps and plans on the existing geodetic network has been assessed. To create topographic maps and plans in accordance with the requirements of regulations, the necessary completion of the geodetic network on the territory of Chernivtsi oblast is calculated.
Геодезичне забезпечення території Чернівецької області (історія, сучасний стан)
Keywords: геодезія; топографія; геодезичне забезпечення